El escalonamiento vegetal de Los Andes occidentales a la latitud de Valparaíso (33° S.) - Quintanilla, Victor G. (Investigaciones Geográficas: Una mirada desde el sur, 1978)
Approximately in the 33 degree of southern latitude, the occidental Andes mountains shows an altitudinal vegetation distribution from the 800 to the 3500 meters. The local -ecologycal conditions and the effects of the altitude don't permit observe a clear sucession in the vegetable-level-represented in this area. In a general way speaking, the MOUNTAIN-LEVEL still conserve a number of sclerophyllous evergreen trees representatives typicall from valley and lowlands (Lithraea caustica, Quillaja saponaria, Maytenus boaria). By the other side, the SUBANDINE LEVEL presents a number of new exponents with an high-adaptability characteristic (Colliguaya, Kageneckia, Escallonia). Over 200 meters of altitude, the ANDINE_LEVEL shows a low and disperse shrub associated with grass and perennial gramineous (Adesmia, Calceolaria, Berberis, Laretia, Stipa), short grassland with andine meadows. Usually moist much of the summer due to melt water. A little bovine and caprine grazing is practiced in the fertile plains sectors. In a general way speaking, must be said that this region is being exposed to the degradation done by the felling of trees, grazing and tourism effects